The implementation and preliminary evaluation of an ART strategy in Mexico: a country example - Vera Heriberto Hermosillo; Luengas Elisa Quintero; Namihira Delia Guerrero; Díaz Dante Sergio Suárez; Muñúzuri Jorge Alejandro Hernández; Christopher J. Holmgren (University of São Paulo, 2009)
The massive use of preventive measures in Mexico including fluoride toothpaste, a national program of salt fluoridation and education on prevention has resulted in a large decline in dental caries over the past two decades. There does however remain a largely unmet need for restorative treatment. This paper describes the steps leading up to the adoption of a strategy, as part of general health policy, to use Atraumatic Restorative Treatment (ART) within the Mexican public health service as a means to address this. This included the development of training materials, the organization of training courses for existing dentists and the incorporation of ART into the undergraduate curriculum. RESULTS: Six years after the introduction of ART in the year 2000, it was estimated that over 2 million ART procedures had been provided. As part of the planning cycle, an evaluation was undertaken in 2008 to determine amongst Mexican dentists what were the perceived problems when implementing the ART approach. Such research identified that the scarcity of appropriate dental materials and the lack of suitable instruments were the major problems. In addition, a preliminary evaluation of ART restorations and sealants placed as part of this National Oral Health Program was undertaken. The survival outcomes after one year compared favorably with one other study conducted in Mexico but were somewhat lower than the results reported from a number of other countries. CONCLUSION: The ambitious and forward thinking policy for improving the oral health in Mexico is now showing dividends. One example is the ART strategy, which has been successful both in terms of the number of ART procedures provided and generally in terms of clinical outcomes.